CULTIVATING JUNIOR HIGH SCHOOL STUDENTS’ CRITICAL THINKING SKILLS BY USING A SHORT-VIDEO IN ENGLISH LANGUAGE CLASSROOM - Atayeva M.; Ciptaningrum D. S.; Hidayah R.; Kassymova G. K.; Dossayeva S. K.; Akmal A. (Scientific Journal of Pedagogy and Economics, 2019)
An effective teaching method for cultivating students’ critical thinking skills of Junior High School students in Indonesia is very necessary as their critical thinking ability is still low. This research is a descriptive study which aims at cultivating learners’ critical thinking by using a short-video since it is believed that technology can motivate the students to learn, increase their interest, engage them to the lesson matter, provide effective learning activities, and demand them to think critically and creatively. The subjects of this study were 130 students of grade IX of State Junior High School 1 (henceforth SMP N 1) Sedayu, Yogyakarta. The students were homogeny in term of age, economic, and social background as well as in English language scores. Facione’s critical thinking rubrics were used to indicate the level of students’ critical thinking in terms of their interpretation, analysis, evaluation, inference, explanation, and self-regulation skill of a short-video. The average score of all items in pre-test critical thinking skills was at fair level with the score 9 out of 20. The results revealed that the students’ interpretation skills were fair with the score of 9 out of 20; analytical skill was 12 out of 20; evaluation skill was 9 out of 20; self-regulation was in fair criterion with the score of 5 out of 10 and good level of explanatory’s skill with the score 6 out of 10, while 12 for inferences. Thus, it can be concluded that the critical thinking skill of the students of grade IX of SMP N 1 Sedayu, Yogyakarta, was still unsatisfactory due to their fair levels. The use of a short-video as an instrument cannot improve their critical thinking skills. It is, therefore, recommended to practice more pertaining to the critical thinking for the students by using any similar instrument.